Investigação da influência do tamanho das partículas de materiais pulverulentos sobre a força de adesão em diferentes substratos aplicando a técnica centrífuga - Felicetti, Marcos Alceu (Universidade Federal de São Carlos, 2008)
It was investigated in this work the influence of the size of the particles of the organic and inorganic powdery material on the force of adhesion of those particles and a built substratum of different materials: stainless steel, PVC, Teflon and glass, applying the centrifuge technique for different compression speeds and detachment. It was used for so much a centrifuga (MA - 860, Marconi Equipamentos), whose maximum speed of rotation is of 14000 rpm. The centrifugal speed is generated to promote the compression (press-on) and the detachment (spin-off) of the particles on the surface of the substratum. A program of analysis of images (Image-Pro Plus 4.5) it was used for the collection and the treatment of the images. To determine the adhesion force being used the centrifuge technique, in the headstock of the centrifuga it was necessary to install two tubes, built in aluminum, for the contention of the adapters, also built in aluminum. The purpose of the adapters was of sustaining the substratum containing the particles of the powdery material. After the application of the centrifugal speed of ompression (press-on) and of the count of the particles initially stuck in the surface of the substratum, for the program of analysis of images, the substratum came back for the centrifuga for the application of the centrifugal speed of detachment (spin-off) in different rotation speeds. After each increase of the speed rotacional, the number of remaining particles of the compression was monitored. The material inorganic powdery, phosphatic rock (ρp = 3,07 g/cm3 and dp = 39,38 µm), and the organics, manioc starch (ρp = 1,49 g/cm3 and dp = 25,24 µm) and corn starch (ρp = 1,47 g/cm3 and dp = 23,08 µm), they were the powders used in the investigation of the influence of the force of adhesion particle substratum applying the centrifuge technique. The criterion of choice of the materials for the construction of the substratum and of the type of used powdery material it was your employability in the industry. The diameter strips studied for those powdery materials they were of 8 13 µm, 13 18 µm, 18 23 µm, 23 28 µm and 28 33 µm. The particles of each powdery material were pressed initially on the surface of the substratum centrifuged to a centrifugal speed of private compression, and immediately after this phase, the adhesion profile was determined. All the powders obeyed a log-normal distribution of percentage of particles stuck in relation to adhesion force. It was obtained the force of geometric medium adhesion for all the powders and it was verified that there was a lineal increase with the force of compression applied initially. For polydisperse particles stuck on a surface, the necessary force to separate the particles varies proportionally to your size. And the adhesion force among the particles of the powdery materials used in the experiments and the surface of the different substratum, increased with the increase of the size of the particles and with the increase of the centrifugal speed of compression (press-on). the order of adherence indicated the following relationship for the powdery materials: manioc starch > phosphatic rock, and for the substratum: glass > stainless steel > PVC > Teflon. Using the experimental results in this work, was considered an equation to represent in a more general way the experimental data obtained for the two powdery materials
Keywords: Ar poluição; Força de adesão; Técnica centrífuga; Van der Waals, Forças de; Compressão e desprendimento de partículas; ENGENHARIAS::ENGENHARIA QUIMICA